Modifying redox potential and its impact on metabolic fluxes in Saccharomyces cerevisiae - Jain, Vishist Kumar (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Science) (Viticulture and Oenology. Wine Biotechnology))--University of Stellenbosch, 2010.